Shareholder governance, bondholder governance, and managerial risk-taking - King, Tao-Hsien Dolly; Wen, Min-Ming (Journal of Banking & Finance, 2011)
We examine the relation between the overall corporate governance structure and managerial risk-taking behavior. We find that the overall governance structure has a significant impact on how managers make decisions on investment policy: strong bondholder governance motivates more low-risk investments such as capital expenditure and lower high-risk investments such as R&D expenditures, whereas weak shareholder governance (entrenched managers) leads to more R&D expenditures. Moreover, we find that the effects of governance on investment policy differ significantly between speculative and investment-grade firms. For speculative firms, strong bondholder or shareholder governance leads to more capital expenditures and low R&D investments. For investment-grade firms, strong bondholder or shareholder governance leads to low capital expenditures and an insignificant impact on R&D investments. Furthermore, financing and investment covenants exhibit strong binding power to deter risky investments. Finally, a more dependent (or a less independent) board is associated with low capital expenditures and high R&D investments.